Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Tekstil dan Garmen Yang Terdaftar di Bursa Efek Indonesia - Siahaan, Yannuke Patricia; Butar Butar, Monetarist; Silaban, Vebri Lamtarida (JURNAL MUTIARA AKUNTANSI, 2022)
In general, funders have the main objective of obtaining optimum net profit. The phenomenon that occurs in this research is the relationship between asset returns, return of equity prices and fluctuating stock prices in the 2016-2021 period. This study aims to determine the impact of asset returns and unilateral equity returns as well as stock price growth. The sample in this research is garment and textile companies listed on IDX for the 2016-2021 period, which is 6 industries. Data collection is done by collecting secondary data. The data analysis technique used is multiple linear regression, namely 1.974+0.028-0.236. The results of this study indicate that partially Return On Assets (ROA) has an effect on stock prices and the Return On Equity (ROE) variable has no effect on stock prices and based on the F test together Return On Assets (ROA) and Return On Equity (ROE). ) has a significant effect on stock prices. The determination test shows that Return On Asset and Return On Equity have an effect of 93.5%. while 6.5% is influenced by other variables not examined in this study.